Calcium fortification of flour-based chips - Puyat, Marife Bawa; Dumelod, Benelyn Domingo (2004)
ABSTRACT The main interest of the study was to develop a calcium-fortified snack chip as a response to the growing concern on osteoporosis and other calcium deficiencies in the country. Two recipes of flour-based chips were evaluated and the more acceptable formulation was fortified. The fortificants used were calcium gluconate and calcium lactate but the former was rejected because of its incompatibility with the product. The calcium-fortified flour-based chips produced and the control were evaluated and were found to have no significant difference in terms of their sensory attributes except for color alone. Both the control and fortified chips were moderately liked based on their overall appearance, saltiness, spiciness, crunchiness and overall acceptability. The production of calcium-fortified flour-based chips was also found to be reproducible after the samples from three different production batches showed no significant differences. Cost comparison between the control and the fortified chips showed that the fortified product is 7.16% costlier than the control. Also, comparison of the costs of the fortified chips with a similar product that is commercially available revealed that the former costs 15.2% higher. Characterization of the control and fortified samples showed that both were microbiologically stable. Finally, through AAS, a 100-g serving of the calcium-fortified flour-based chips was found to provide 40% of the RENI for calcium for Filipinos ages 19-49 years as compared to the unfortified chips which provide only 0.01%
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Calcium; Enriched foods; Snack foods